Avaliação como dispositivo de controle de um currículo neoliberal do Estado de São Paulo - Guidote, Andresa Giseli Piane (Universidade Federal de São Carlos, 2025)
This research aims to analyze the evaluation of Basic Education in the State of São Paulo as a control device to support a curriculum with neoliberal characteristics. For this problematization, school assessment is conceived as a control device, using the philosopher Michel Foucault's being-power theoretical basis. The research methodology is bibliographic in nature and is based on the official documents of Basic Education in the State of São Paulo. The research is based on four pillars: Neoliberalism, Assessment, the São Paulo Curriculum and Michel Foucault's Being-Power Theory. In this process of analyzing the bibliographic material, we noticed neoliberal trends in the educational field, with a view to evaluating the São Paulo curriculum with an emphasis on results, on the classification of subjects, according to the performance data obtained in the centrality and the norm, in order to promote regulation as a rule for homogenization, exercising surveillance, punishment and competition as the bases of an evaluative society.
Assessment as a control device for a neoliberal curriculum in the State of São Paulo
La evaluación como dispositivo de control de un currículum neoliberal en el estado de São Paulo
Keywords: Avaliação Escolar; Neoliberalismo; Teoria Foucaultiana; Currículo Paulista; School Assessment; Neoliberalism; Foucauldian theory; Paulista Curriculum; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::CURRICULO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM